2021
DOI: 10.3390/life11101044
|View full text |Cite
|
Sign up to set email alerts
|

Small Extracellular Vesicles: Functions and Potential Clinical Applications as Cancer Biomarkers

Abstract: Cancer, as the second leading cause of death worldwide, is a major public health concern that imposes a heavy social and economic burden. Effective approaches for either diagnosis or therapy of most cancers are still lacking. Dynamic monitoring and personalized therapy are the main directions for cancer research. Cancer-derived extracellular vesicles (EVs) are potential disease biomarkers. Cancer EVs, including small EVs (sEVs), contain unique biomolecules (protein, nucleic acid, and lipids) at various stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 154 publications
(162 reference statements)
0
12
0
Order By: Relevance
“…Cancer-derived sEVs promoted the spread and colonization of cancer cells by remodeling the tumor microenvironment and altering the extracellular matrix [ 68 ]. Cancer sEVs play a role in six major areas: angiogenesis, epithelial mesenchymal transition (EMT), invasive metastasis, immune escape, cancer-associated fibroblasts (CAFs), and drug resistance [ 69 ]. UBL3 may influence these processes by being involved in sorting proteins into sEVs.…”
Section: Ubl3mentioning
confidence: 99%
“…Cancer-derived sEVs promoted the spread and colonization of cancer cells by remodeling the tumor microenvironment and altering the extracellular matrix [ 68 ]. Cancer sEVs play a role in six major areas: angiogenesis, epithelial mesenchymal transition (EMT), invasive metastasis, immune escape, cancer-associated fibroblasts (CAFs), and drug resistance [ 69 ]. UBL3 may influence these processes by being involved in sorting proteins into sEVs.…”
Section: Ubl3mentioning
confidence: 99%
“…sEVs are typically less than 200 nm in diameter [ 6 ] and are produced in the extracellular space by nearly all cell types [ 26 ]. The number and content of sEVs are related to the state and type of the producing cell, which is caused by the distinct regulatory sorting mechanisms of the source cells [ 27 ].…”
Section: Sev Isolation and Detectionmentioning
confidence: 99%
“…In summary, sEVs play a crucial role in gynecologic malignancy diagnosis and treatment. For example, sEV miRNAs have been shown to be reliable biomarkers for early detection and can predict treatment response [ 6 ]. Clinical diagnosis of gynecologic malignancy using sEVs has been extensively investigated ( Table 2 ).…”
Section: Sev and Emsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the disbalance of exosomes containing miR-217 was considered a diagnostic biomarker in gastric cancer [ 19 ]. Recent work indicated that exosomes containing miR-9-3p or miR-21 can act as biomarkers for early detection of metastasis in liver cancer (HCC), a malignant cancer that has no specific symptoms in the early stages [ 20 ]. In this review, we describe the functional and mechanistic roles of exosomes in the development and progression of gastrointestinal cancers.…”
Section: Introductionmentioning
confidence: 99%